The level of student's alertness toward takaful: The case study at University Malaysia Kelantan (UMK) - Anney Sofia Abd Wahab; Fatin Hanisah Abdul Latif; Marniza Agustiar; Muhammad Arif Aiman Hassan (2022)
Muslims are encouraged to plan their lives economically and financially to achieve the objectives of Maqasid Shariah. In order to achieve that, one of the methods apply in takaful. In the event of a medical emergency, Takaful plan with medical benefits might be valuable as a safety net as well as a financial buffer. In the event of an emergency, takaful will alleviate the financial load. The scope of this research paper will focus on the level of alertness towards Takaful among students in University Malaysia Kelantan City Campus. This study's purpose is to investigates the factors influencing alertness of takaful product to UMK’s students. The method used in this research is qualitative. The study was conducted using the interview to collect information from four random students of UMK. Four themes emerged which is the takaful alertness, background education, religion, and income level. The findings of this study revealed that the majority of UMK students are aware of takaful, although only to a limited extent. However, just several students are still under the impression that takaful is just for Muslims. However, the research indicated that there is still a slightest chance that a few students aware but do not really practicing it due to the lack of exposure among them. This study highlights the insights to explore more about the takaful. Thus, it would provide a knowledge to fellow Muslims and lastly it would inflict Malaysian government and other Muslim countries to be alert the need of takaful. The contributions and recommendations are then put forward for future research.